The Effect Of The Number Of Msmes, Labor, And Local Original Income On Economic Growth In North Luwu Regency - Wanda Pratiwi; I Ketut Patra; Jusman (LP2M IAIN Palopo, 2026)
Abstract This study aims to analyze the influence of the number of MSMEs, labor, and Regional Original Income (PAD) on economic growth in North Luwu Regency. The research hypothesis states that these three variables have a significant influence both partially and simultaneously on regional economic growth. The research method uses a quantitative approach with an explanatory nature, based on secondary time series data for the period 2014–2023. The analysis was carried out using multiple linear regression using the Cobb Douglas model using SPSS software version 26. The variables studied include the number of MSMEs, labor, PAD, and ecoomic growth (GRDP at constant prices). The results show that partially, the number of MSMEs, labor, and PAD do not have a significant effect on economic growth. However, simultaneously, the three variables are proven to have a significant effect with a calculated F value of 10.118 and a significance of 0.009. The Adjusted R² value of 0.112 indicates that the influence of the three variables is relatively small, while 88.8% of the variation in economic growth is influenced by other factors outside the model. The implications of this research emphasize the need for evidence-based policies to strengthen MSMEs through digitalization and training, improve workforce quality, and allocate regional revenue (PAD) to productive sectors to ensure more inclusive and sustainable regional economic growth. Keywords: MSMEs, workforce, PAD, economic growth, North Luwu